(untitled) (Medical Forum Monthly, 2021)
Objective: To compare complications of hemodialysis in pre and post transplanted renal failure patients; to determine the prevalence of observed complications; to evaluate underlying comorbid illness between two groups. Study Design: A cross-sectional study observational study Place and Duration of Study: This study was conducted at the department of Nephrology in Nishtar Medical University & Hospital Multan from July 2020 to December 2020 for a period of six months. Materials and Methods: 100 patients with confirmed renal failure and on hemodialysis treatment were included in the study. Among them, 50 never had a transplant while other half were on dialyses after graft rejection. Patients were observed during hemodialysis and symptomatic complications were recorded. In addition, medical history of participants was obtained to evaluate underlying comorbidities. SPSS 25.0 was used for statistical evaluation. One way analyses of variance (ANOVA) and student’s t-test were used to compare two study groups. Results: A total of 100 patients of renal failure underwent conventional HD. Patients from Bothe the groups showed no significant difference in basic characteristics. However, significant difference (p>0.05) was found between frequency of acute complication between two groups. Similarly, higher incidences of variable comorbidities is found among graft rejected renal failure patients. Conclusion: Hemodialysis act as the major life saving maintenance treatment among renal failure patients. However, multiple complications are associated with this therapeutic approach. Given the findings, it is suggested to modify dialysis procedures to mask the effects of underlying comorbidities during dialysis especially for the graft rejected renal failure patients.